Digitalisasi dan Publikasi Nilai Kesejarahan Benda Purbakala Pura Puseh Desa Adat Kemenuh, Kecamatan Sukawati, Kabupaten Gianyar - I Gusti Ngurah Tri Adi Citarsa; I Komang Suyanta; Anugerah Banyu Bela Justitia; I Nyoman Widya Paramadhyaksa; Gusti Agung Ayu Putri; I Made Agus Julianto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Puseh Kemenuh Temple is one of the temples in Kemenuh Village, Sukawati District, Gianyar Regency, with various archaeological remains. Its existence still needs to be widely known by the public. The utilization of digitalization in developing tourism villages and educational tourism has yet to be developed. The Udayana University KKNT Team Period IV Year 2024 has a focus on activities in the form of developing digital education for Puseh Kemenuh Temple consisting of Architecture students who play a role in drawing the location of archaeological relics, Information Technology students designing websites and Archaeology students in charge of recording archaeological relics stored. The implementation method used is interviews, observations around Puseh Kemenuh Temple, and literacy data needed to realize this activity. This team works together to provide an overview and make it easier for the surrounding community to obtain information about archaeological remains at Puseh Kemenuh Temple.